Does economic agglomeration affect the sustainable intensification of cultivated land use? Evidence from China - Xianhui Hou; Yuqing Yin; Xin Zhou; Minjuan Zhao; Lan Yao; Daojun Zhang; Xiangdong Wang; Chuyu Xia (Ecological Indicators, 2023)
The sustainable intensification (SI) of cultivated land use (CLU) is important for achieving global sustainable development goals (SDGs). However, in the rapid advancement of agglomeration economies, it remains unclear whether economic agglomeration (EA) affects SI. Combined with emergy theory, this study utilized socioeconomic and natural environment data from 31 provincial administrative regions from 1990 to 2017 to evaluate the SI level in China. It further analyzed the impact of EA on SI using a spatial econometric model that includes mediating effects. The results showed that the EA level in China continued to rise, whereas the SI level continued to decline from 1990 to 2017. The mediating effect analysis showed that fiscal support for agriculture and agricultural labor productivity have a suppression effect of |−4.186|% and |−2.002|% in the local region, while cultivated land-use intensity has partial mediation of 6.350% in the local region; and agricultural labor productivity has a suppression effect of |−4.680|% on the surrounding region, while cultivated land-use intensity has stronger partial mediation relative to the local region, even up to 10.402% on surrounding regions. This implies that the impact of EA on SI involves complex paths and spatial differences. This study provides a better understanding of the reasons for the continuous decline in the SI in agglomeration-type economic development and feasible policy proposals.